Pengaruh Insentif Dan Kualitas Komunikasi Terhadap Motivasi Kerja: (Studi kasus pada tenaga harian lepas Dinas Perumahan Rakyat, kawasan permukiman dan lingkungan hidup Kabupaten Ciamis) - Kumalawati Dewi (Transformasi: Journal of Economics and Business Management, 2023)
This research is motivated by the existence of problems where iIncentives are still lacking so that they affect employee motivation. There is still little ability to communicate between records. Still low employee motivation. Employees are less responsible in carrying out work in accordance with accountability. The risk indicators have not been implemented which is marked by the assigning employee to carry out the assigned task quickly and precisely, the less optimal execution of the signing of the marker, marked by the lack of desire of the employee to be successful at work by increasing performance by obtaining a score of 52%. Incentives affect enthusiasm at work. Poor communication between employees affects work motivation, thus the purpose of this study is to determine the effect of incentives and the quality of communication on work motivation in the Public Housing, Settlement Area and Environment (DPRKLH) Office of Ciamis Regency. The research method used is quantitative descriptive with the results of research that incentives tend to be high, as well as high employee motivation. Thus, the incentives affect the work motivation of employees of the freelance daily workers of the Public Housing, Residential Areas and Environment Office of Ciamis Regency. The highest average score obtained from the research results is found in the supporting indicators. Meanwhile, the lowest average value is found in work performance indicators. The quality of communication tends to be high, as well as high employee motivation. Thus, the quality of communication has an effect on the work motivation of the employees of the freelance workers of the Public Housing, Settlement Areas and Environment Office of Ciamis Regency. This means that if the quality of communication increases, employee motivation also increases. As for the acquisition of the highest average score from the results of the study found on the communicant indicator. Meanwhile, the lowest value is found in the media indicator. Incentives and quality of communication tend to be high, as well as high employee motivation. Thus, the incentives and quality of communication have an effect on the motivation of employees of the freelance daily workers of the Public Housing, Settlement Areas and Environment Office of Ciamis Regency.